Measuring uncertainty and its effects in a small open economy - Miguel Cabello; Rafael Nivin (Graduate Institute of International and Development Studies, 2022)
In the aftermath of the 2008 Global Financial Crisis (GFC), scholars and policymakers turned their attention to the role of uncertainty in amplifying the effects of economic or financial shocks on economic activity. A growing literature has focused on addressing this question. Most works find that uncertainty provides an additional transmission mechanism for recessionary shocks, which amplifies their negative effects on the economy. Nonetheless, most of these studies focus on developed economies. It is important to study the effects of uncertainty in the context of small open economies as, unlike developed countries, they are subject to uncertainty from both external and domestic sources. Along these lines, this paper seeks to assess the effects of uncertainty on economic performance in a small open economy and establish the relative importance of external and domestic uncertainty. By using an extended methodology to estimate, simultaneously, a conditional mean model and a stochastic volatility factor model, it is possible to estimate reliable uncertainty measures and describe their distinct dynamics. The impulse-response analysis shows that rising uncertainty produces negative effects on economic activity in a small open economy, and the largest effects happen when external uncertainty climbs. However, we found an intriguing effect: when uncertainty rises, business loans tend to increase immediately after the shock, but return rapidly to their equilibrium level.
Keywords: E44; C11; C13; C32; C55; 330; Uncertainty; Stochastic volatility; Dynamic Factor models